2014
DOI: 10.1210/jc.2013-2781
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Socioeconomic Disparities in Presentation and Outcomes of Well-Differentiated Thyroid Cancer

Abstract: Black patients and those with low SES have worse outcomes for thyroid cancer. API and Hispanic patients may have a protective effect on survival despite presenting with more advanced disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
98
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(114 citation statements)
references
References 31 publications
10
98
0
3
Order By: Relevance
“…Many, but not all (17), studies have found poorer survival in men with DTC (9,10,18,19). While a previous study concluded that the apparent survival disadvantage among men overall resulted from a larger percentage of men diagnosed with advanced stage disease, in young men there was a small, statistically significant survival disadvantage for stage 1 papillary thyroid cancer and suggestive survival disadvantage in stage 2 papillary thyroid cancer (18).…”
Section: Discussionmentioning
confidence: 98%
“…Many, but not all (17), studies have found poorer survival in men with DTC (9,10,18,19). While a previous study concluded that the apparent survival disadvantage among men overall resulted from a larger percentage of men diagnosed with advanced stage disease, in young men there was a small, statistically significant survival disadvantage for stage 1 papillary thyroid cancer and suggestive survival disadvantage in stage 2 papillary thyroid cancer (18).…”
Section: Discussionmentioning
confidence: 98%
“…The results of this study show that race has an impact on survival in patients with papillary thyroid 12 Their study included 25 945 patients from the California Cancer Registry diagnosed with thyroid cancer from 1999 to 2008. They found that racial minority groups and patients with low socioeconomic status had a higher likelihood of presenting with metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that racial minority groups and patients with low socioeconomic status had a higher likelihood of presenting with metastatic disease, and had an increased risk of mortality. 12 Yu et al evaluated risk factors for mortality in patients with papillary thyroid microcarcinoma. 13 They found that African American or minority race was associated with an increased risk of mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Harari and colleagues have published that Black patients and those with a low socioeconomic status (SES) have worse outcomes for differentiated thyroid cancers than their White and higher SES counterparts (3). Similarly, Keegan et al recently published that adolescents and young adult patients residing in low SES neighborhoods and nonmetropolitan areas had worse thyroid cancer-specific survival among adolescent and young adult men (4).…”
Section: Introductionmentioning
confidence: 99%